In silico prediction of telomerase reverse transcriptase inhibitors using modified retinol for the treatment of arsenical cancer - Tshering, Kipchu; Misbahuddin, Mir (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Retinol molecule was modified to predict the inhibitors of telomerase reverse transcriptase for the treatment of arsenical cancer through in silico study. Telomerase activity is expressed in the cancerous conditions which can be the target for anticancer activity by inhibiting telomerase reverse transcriptase enzyme. The inhibitors were predicted through molecular docking of modified retinol with telomerase reverse transcriptase. Taking into account of low binding energy and high binding affinity two new compounds, compound number 606 and compound number 609 were predicted as the inhibitors of telomerase reverse transcriptase for the treatment of arsenical cancer. The prediction of these two compounds was further supported by drug-likeness test through Administration, Distribution, Metabolism, Excretion and Toxicity evaluation. The compounds were also compared with some of the known inhibitors of telomerase reverse transcriptase.